Where the sidewalk ends : the poems & drawings of Shel Silverstein. - Silverstein, Shel. (New York : HarperCollinsPublishers, 2002)
A boy who turns into a TV set and a girl who eats a whale are only two of the characters in a collection of humorous poetry illustrated with the author's own drawings. Come in - for where the sidewalk ends, Shel Silverstein's world begins. The Unicorn and the Bloath live there, and so does Sarah Cynthia Sylvia Stout who will not take the garbage out. It is a place where you wash your shadow and plant diamond gardens, a place where shoes fly, sisters are auctioned off, and crocodiles go to the dentist.
NP
Keywords: Humorous poetry, American; Children's poetry, American; Humorous poetry